Pengaruh Struktur Kepemilikan Keluarga dan Profesionalisasi Manajemen terhadap Kualitas Corporate Governance pada UMKM di Indonesia - Rista Evania; Via Amelia; Rica Khabibah Tuzakia; Lilian Syalsyah Beella; Nadia Tri Susanti; Dina Amanda; Rizzah Umamy Maulidiyah (CV. ALIM'SPUBLISHING, 2026)
This study aims to analyze the influence of family ownership structure and management professionalization on the quality of corporate governance in Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Family-owned MSMEs dominate the Indonesian business sector and play a significant role in national economic growth. However, the implementation of corporate governance in many MSMEs remains a challenge due to the dominance of family control and limited managerial capabilities. This research employed a quantitative approach using a survey method. Primary data were collected through questionnaires distributed to 50 MSME owners and managers. The data were analyzed using multiple linear regression to examine the effect of family ownership structure and management professionalization on corporate governance quality. The findings indicate that family ownership structure has a positive and significant effect on corporate governance quality. Management professionalization also demonstrates a positive and significant influence and shows a stronger contribution compared to family ownership structure. Simultaneously, both variables significantly affect corporate governance quality in Indonesian MSMEs. The study implies that maintaining a balance between family involvement and professional management practices can improve governance quality, strengthen organizational accountability, and support long-term business sustainability.